586 Peri-Pancreatic Migration of Lost Intra Uterine Device: Case Report and Review of Literature. (12th October 2021) - Bhattacharya, P; Amada, H; George, A
Abstract: Intra uterine devices (IUDs) is one of the most effective form of contraception available today. Uterine perforation and IUD migration is a rare but serious complication and is reported to occur in 0.05 to 13 cases out of 1000 IUCD placements. Migration of IUD to pelvis and lower abdominal organs following uterine perforation has been reported widely in literature. However far migration into the upper abdomen in very rare. Here we report a case asymptomatic peri-pancreatic migration of IUD. A 65-year-old lady being investigated for pneumonia was picked up to have an asymptomatic IUD lying in front of the pancreas. The patient recalled having a hormonal Mirena coil placed 12 years previously for menopausal symptoms. Routine 3-year general practitioner follow-up failed to detect the IUD on vaginal examination. The patient denied spontaneous IUD discharge. However, three subsequent pelvic ultrasound scans did not detect any retained IUD and she was discharged as unrecognized IUD expulsion. She remained asymptomatic for the next 12 years with no abdominal symptoms though she did report to the General Practitioner, multiple episodes of new onset hot flushes when opening bowels - which was managed conservatively with reassurance. It was decided to surgically remove the IUD. Intraoperatively, the IUD was found densely adherent to the lesser omentum close to the pancreas and stomach and was removed safely laparoscopically. The patient made a good postoperative overnight recovery and was discharged. Intra-abdominal migration of IUDs is a very rare complication of IUD insertion and when detected should be promptly treated with Laparoscopic removal.